PENGARUH BRAND IMAGE, ONLINE CUSTOMER REVIEW DAN ONLINE CUSTOMER RATING TERHADAP KEPERCAYAAN KONSUMEN PADA SHOPEE DI DESA TEGAL TUGUKECAMATAN GIANYAR - Anggreni, I Dewa Ayu Wulan; Wijaya, Bagus Arya; Diatmika, I Kadek Dwi; Rizkianti, Anggun Wida (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2024)
The study's objectives were to ascertain if brand image, online customer reviews, and online customer ratings had a concurrent, partial, and substantial impact on consumer trust in Shopee in Tegal Tugu Village, Gianyar District. By establishing criteria, such as customers who reside in the Tegal Tugu Village area of Gianyar District, have the Shopee application, have transacted using Shopee more than once, and are above the age of 17, the purposive sampling approach was used to calculate the number of samples from 97 consumers. The traditional assumption test, multiple linear regression analysis, determination analysis, F-test analysis, and t-test analysis were all used to examine the data. The findings demonstrated that there was either a simultaneous or partial positive and substantial impact.